Peripubertal pregnancies and associations with health and developmental outcomes in offspring during late adolescence and adulthood: sibling-comparison register study - Vasudha Ahuja; Ayako Hiyoshi; Helena Backman; David Simmons; Scott Montgomery (International Journal of Epidemiology, 2026)
Abstract Background We examined the association of peripubertal pregnancies with long-term health and developmental outcomes in adult offspring and strengthened causal inference using sibling-comparison methods. Methods Using linked Swedish register data from 1964 to 2018, we conducted a cohort study to estimate associations of pregnancies before age 16 years compared with pregnancies between ages 16 and 25 years, with body mass index (BMI), systolic blood pressure (SBP), cognitive function, and stress resilience among 943 444 male offspring aged 17–21 years in the Military Conscription Register. We further assessed associations with type 2 diabetes (T2D), depression, and anxiety among 2 461 510 male and female offspring aged 18–73 years using population-wide registers. Linear, multinomial, and survival models were used. Sibling fixed-effect models were used to account for unmeasured confounding shared among siblings. Results Offspring from pregnancies before age 16 years compared with pregnancies between ages 16 and 25 years had lower SBP (β − 1.12; 95% confidence interval [CI] − 1.97 to −0.26), poorer cognitive function (β − 0.54; 95% CI −0.67 to −0.40), and poorer stress resilience (β −0.24; 95% CI −0.38, −0.10). There was no increased risk of being underweight or overweight compared with normal weight. There was a lower risk of anxiety (hazard ratio 0.87; 95% CI 0.80 to 0.95) and no increased risk of T2D or depression. Sibling-comparison analyses attenuated deleterious associations to null or reversed them and amplified associations with markers of better health. Conclusion Pregnancies before age 16 years may not be causally associated with adverse long-term health and developmental outcomes in adolescent and adult offspring. The adverse associations in conventional analyses appear attributable to shared familial characteristics.